Theoretical spectra and energetics for c-C3HC2H, l-C5H2, and bipyramidal D3h C5H2 - Watrous, Alexandria G.; Westbrook, Brent R.; Fortenberry, Ryan C. (Frontiers in Astronomy and Space Sciences, 2022)
The recent astronomical detection of c-C3HC2H and l-C5H2 has led to increased interest in C5H2 isomers and their relative stability. The present work provides the first complete list of anharmonic vibrational spectral data with infrared intensities for three such isomers as well as including the first set of rotational data for the bipyramidal C5H2 isomer allowing for these molecules to serve as potential tracers of interstellar carbon. All three isomers have fundamental vibrational frequencies with at least one notably intense fundamental frequency. The l-C5H2 isomer has, by far, the highest intensities out of the three isomers at 2076.3 cm−1 (738 km mol−1) and 1887.5 cm−1 (182 km mol −1). The c-C3HC2H isomer has one intense peak at 3460.6 cm−1 (84 km mol−1), and the bipyramidal C5H2 isomer has one intense peak at 489.3 cm−1 (78 km mol−1). The relative intensities highlight that while l-C5H2 is not the lowest energy isomer, its notable intensities should make it more detectable in the infrared than the lower c-C3HC2H form. The bipyramidal isomer is firmly established here to lie 44.98 kcal mol−1 above the cyclic form. The explicitly correlated coupled cluster rovibrational spectral data presented herein should assist with future laboratory studies of these C5H2 isomers and aid in detection in astronomical environments especially through the newly operational James Webb Space Telescope.